The Effects of Marine Carbohydrates and Glycosylated Compounds on Human Health - Kang, Hee-Kyoung (Int J Mol Sci, 2015)
Marine organisms have been recognized as a valuable source of bioactive compounds with industrial and nutraceutical potential. Recently, marine-derived carbohydrates, including polysaccharides and low molecular weight glycosylated oligosaccharides, have attracted much attention because of their numerous health benefits. Moreover, several studies have reported that marine carbohydrates exhibit various biological activities, including antioxidant, anti-infection, anticoagulant, anti-inflammatory, and anti-diabetic effects. The present review discusses the potential industrial applications of bioactive marine carbohydrates for health maintenance and disease prevention. Furthermore, the use of marine carbohydrates in food, cosmetics, agriculture, and environmental protection is discussed.